Prevalence and risk factors of knee osteoarthritis: a cross-sectional survey in Nanjing, China - Shao, Wenjuan; Hou, Huisheng; Han, Qi; Cai, Keshu (Frontiers in Public Health, 2024)
BackgroundKnee osteoarthritis (KOA) presents a significant public health challenge due to its hazards and increasingly severe trends. Addressing this challenge requires targeted investigation into the prevalence and identification of risk factors for KOA across different regions, especially in populous and vast China. Therefore, a cross-sectional survey was conducted in Nanjing, China, with the aim of investigating the prevalence and risk factors of KOA among individuals aged 50 and above.MethodA total of 1,045 subjects were selected using the stratified random sampling method and diagnosed with KOA based on the diagnostic criteria established by the Chinese Medical Association. Data on 14 potential risk factors were collected through a self-designed questionnaire and standardized on-site tests. The association between KOA and these risk factors was explored using t-tests, Chi-square tests, and logistic regression analysis.ResultsThe prevalence of KOA among the subjects was 23.64%. Multiple logistic regression models indicated that the risk of KOA was significantly higher among women (OR: 5.34, 95% CI: 3.13–9.11), subjects aged 60–69 (OR: 1.83, 95% CI: 1.25–2.69) and over 70 (OR: 2.87, 95% CI: 1.80–4.59), individuals with high school education and above (OR:2.22, 95% CI: 1.37–3.60), those with flatfoot (OR: 1.74, 95% CI: 1.10–2.74), and subjects classified as overweight (OR: 1.91, 95% CI: 1.21–3.04) and obese (OR: 4.63, 95% CI: 2.18–9.85) based on their BMI status. Additionally, the models identified weight (OR: 1.04, 95% CI: 1.01–1.08), 30-s chair stand performance (OR: 0.94, 95% CI: 0.91–0.97), and single-leg stand performance (OR: 0.96, 95% CI: 0.93–0.99) as independent risk factors for KOA.ConclusionThe prevalence of KOA is remarkable in Nanjing city. The risk factors for KOA include women, older age, higher education, flatfoot, increased weight and BMI, as well as poor performance in 30-s chair stand and single-leg stand tests.